THE IMPORTANCE OF ACCOUNTING INFORMATION SYSTEM PERFORMANCE ANALYSIS - MULYANA, ASEP; Leniany, Tevi (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2025)
This research explains the importance of performance analysis in accounting information systems which aims to analyze how effective and accurate the performance of accounting information systems is on the company's economy. If this accounting information system is not effective and accurate, it will cause several factors such as recording errors, inaccurate reporting of the company's economic financial activities. The method used in this research is a literature study which collects data from several sources. The conclusion of this research is that in the era of information technology, companies are forced to use accounting information systems because this accounting information system is very important for companies. The existence of an accounting information system produces reports and data effectively and accurately and enables managers to make appropriate decisions. Information systems also provide good benefits for companies, such as tax optimization, cost control, accurate budget preparation and reducing the risk of errors in recording.